Keluarga Peduli Stunting Sebagai Family Empowerment Strategy Dalam Penurunan Kasus Stunting di Kabupaten Blora - Denis Oxy Handika (Universitas Lancang Kuning, 2020)
Stunting is a form of growth faltering due to chronic nutrient deficiency that lasts from the womb until the age of 24 months. This situation not only makes the children height short but also manifests an increase in children's morbidity and mortality, as well as children's cognitive, motor, and verbal development which is not optimal it ultimately results in low human resources. Family-based intervention can be an effective step in helping the government reduce the prevalence of stunting. By using the participatory action method in the implementation of empowering family activity for stunting, the people of Jomblang Village, Jepon District, Blora Regency are equipped with knowledge about strengthening 1000 HPK, screening stunting independently, optimizing exclusive breastfeeding, processing breast milk and making MP-ASI based on available resources. around the place of residence. The results of this devoted family empowerment service devotion are increasing community understanding of stunting, 1000 HPK, exclusive breastfeeding, skills in processing milk and community independence skills in making MP-ASI Sujaka.